Interpretasi Bawah Permukaan Daerah Penambangan Batuan Andesit Awang Bangkal Kabupaten Banjar Kalimantan Selatan Menggunakan Metode Magnetik - Ayi Nurhidayah; Sri Cahyo Wahyono; Simon Sadok Siregar (Jurnal Fisika FLUX, 2019)
This research has been done in the mining area of andesite rock of Awang Bangkal village by using magnetic method. Magnetic method is one of the most common geophysical methods used for preliminary surveys on petroleum, earth, and mineral rock exploration. It is intended to determine the subsurface distribution in the area by performing qualitative and quantitative interpretations based on the magnetism value of the earth. The result of data processing using geosoft oasis montaj software shows that the total magnetic field anomaly is -807,3 to -361,7 nT. Qualitative interpretation is done by looking at the contour map of the anomaly, the result of upward continuation and the reduction to the poles. While the interpretation is done by making a modeling of the path that has been determined using mag2dc software. The model shows that the rocks that dominate the area are andesite rocks with their susceptibility value of 0.0992 to 0.2305 in SI units.